"If We Don't Have Diversity, There's No Future to See": High‐school students' perceptions of race and gender representation in STEM. Issue 6 (13th August 2021) - Martin, Anne E.; Fisher‐Ari, Teresa R.
Abstract: The perceptions of students interested in STEM, particularly those too often excluded due to race and/or gender, are necessary to create educational experiences that additively contribute to students' access and inclusion in STEM. The purpose of this inquiry was to understand the perceptions of 34 high‐school students about race and gender representation in STEM. Students participated in a 3‐week, university‐sponsored summer programme geared toward teaching and science, technology, engineering, and mathematics (STEM). At the end of the programme, we interviewed students about STEM in their community, STEM role models, potentially working in a STEM field, barriers to STEM, and why they think White men are disproportionately represented in STEM fields. Guided by a critical framework with an intersectional lens, qualitative content analysis of interview data centered on the descriptive codes "race" and "gender" using a constant comparative analytic approach. Results indicated that participants (1) drew on family role models in STEM, (2) used White privilege and patriarchy at varying levels to explain exclusion from STEM, (3) described limited, stereotypical, and hidden depictions of race and gender in STEM, and (4) often perceived STEM as "pushed" while not explicitly associating STEM with helping, or giving back to their community. Implications drawn from participant perspectives call for educational endeavors that expand dominant conceptions of who and what is considered STEM, center students' families and communities, utilize a problem‐based approach positioning STEM as a tool for social justice, and include direct conversations about gendered racism and stereotypes.